La práctica profesional en la formación didáctica y pedagógica de docentes (2009)
In this paper present a project that examines, analyzes, evaluates and reoriented, from critical and ongoing reflection, the processes of teaching and learning of chemistry as a science, considered as actors in the process: training teachers to hold the schools where develops the professional practice and teaching faculty researchers at the Universidad Distrital. An analysis of the school context in which teachers in training, used the development of teaching units as a strategy to address the concepts, theories or models of chemistry in different degrees and institutions where you did your teaching practice, these teaching units are directed from the problem-solving model